ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK TASIKMADU KARANGANYAR - Anisa; Hartono; Adiningsih, Retnowati (Jurnal Kesehatan Yamasi Makassar, 2025)
Patient satisfaction is an important and crucial indicator of service quality and pharmacy performance. Therefore, pharmacies must be oriented towards patient satisfaction and patient safety in every service provided. Continuous improvement needs to be done in order to maintain service quality. Periodic and continuous evaluation is a must carried out by pharmacies. The purpose of this study was to determine the performance of pharmacies in their pharmaceutical services to patients. This research design is descriptive quantitative with observational methods through prospective studies. The population and sample were customers who had experienced the services of Tasikmadu Pharmacy from February - March 2025 by giving questionnaires to 100 patients of Tasikmadu Pharmacy. Measurement of satisfaction based on servqual dimensions, namely assurance, empathy, responsiveness, physical facilities (tangible), and reliability. Data analysis using Likert scale. Based on the results of the analysis, the level of satisfaction with services in the guarantee dimension at Tasikmadu Pharmacy is very satisfied with a score of 90.91%, the empathy dimension is very satisfied (90.5%), the responsiveness dimension (89.5%), the physical facilities dimension (88.43%), and the reliability dimension (87.17%). The achievement of a satisfaction score of 89.30% in the five dimensions of service indicates that the services at the Tasikmadu Pharmacy are considered very satisfying by patients. However, it is necessary for pharmacies to continue to strive to improve their performance in providing services to patients, especially in the reliability dimension.